Rentabilidad financiera de la Empresa Futurcorp S.A. - García Aguachela, Mary Carmen (2018)
Futurcorp S.A. is a company dedicated to the elaboration of compotes, jams, jellies, purées and other fruit or nut preserves. It is located at Km 1, via Pueblo Old San Juan. He is currently a special taxpayer, and his main source of income is Exporting your products. The present work has the purpose of analyzing the financial statements of the entity, to determine the rate of return obtained by the entity. For this they will be used, as a source, the financial statements of the company for the years 2016 and 2015, because the Financial statements for 2017 are not ready. In addition, the percentage profitability of the sector to make a comparison and identify the variation between both indices, so that the two entities of the sector. It will make use of, interviews to the corresponding administrative personnel, information of the company registered in the control bodies and bibliographic sources for complement the development of the study